Integrating Social Cognitive Theory in English for Office Administration Learning Performance Outcomes: english - Bhagaskoro Kurniawan; Basyiruddin Basyiruddin; Riesca Anindya Septantina (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
This study examines the effectiveness of Social Cognitive Theory (SCT)–based English instruction supported by strategic code-mixing in improving learning motivation and English performance among Office Administration students in an English for Specific Purposes (ESP) context. Using a quantitative quasi-experimental design, the study involved 30 undergraduate students who completed pre-test and post-test assessments as well as a Likert-scale questionnaire measuring SCT-related constructs, including self-efficacy, observational learning, self-regulated learning, and motivation and engagement. Data were analyzed using descriptive statistics, paired-sample t-tests, and Pearson correlation analysis in SPSS to evaluate learning gains and relationships among psychological learning variables. The results indicate a significant improvement in students’ English performance following the instructional intervention, demonstrating the effectiveness of SCT-based pedagogy in strengthening office-related English skills. Questionnaire findings reveal high levels of self-efficacy, observational learning, and self-regulated learning, along with moderate to high motivation and engagement, suggesting enhanced confidence, autonomy, and classroom participation. Correlation analysis shows that self-efficacy, observational learning, and motivation and engagement were significantly and positively associated with students’ final English scores, while self-regulated learning displayed a positive but non-significant relationship, indicating a more gradual impact on performance. Additionally, the strategic use of code-mixing, particularly Bahasa Indonesia, contributed to reducing learner anxiety, improving comprehension, and increasing confidence in professional English communication. Overall, the findings provide empirical evidence that integrating SCT-based instructional strategies with principled code-mixing effectively enhances English proficiency, learner motivation, and workplace communication competence, offering valuable implications for ESP instruction and higher education language teaching